The 40 T Superconducting Magnet Project at the National High Magnetic Field Laboratory - Bai, Hongyu; Bird, Mark D.; Cooley, Lance D.; Dixon, Iain R.; Kim, Kwang Lok; Larbalestier, David C.; Marshall, William S.; Trociewitz, Ulf P.; Weijers, Hubertus W.; Abraimov, Dmytro V.; Boebinger, Greg S. (IEEE transactions on applied superconductivity, 2020)
The National High Magnetic Field Laboratory has launched an innovative project to develop a 40 T all superconducting user magnet. The first year funding was awarded by the National Science Foundation in September 2018. Consideration of a 40 T superconducting user magnet sets target specifications of a cold bore of 34 mm with a homogeneity of 500 ppm over a 1 cm diameter of spherical volume, a better than 0.01 T set-ability and stability, and with an ability to ramp up to full field 50,000 times over its 20 years design lifetime. It will be a fully superconducting magnet that can withstand quenches at its full 40T field and provide a very low noise environment for experimentalists. These capabilities will enable the 40 T SC magnet to support higher-sensitivity measurements than possible in present-day resistive and hybrid magnets; high-magnetic-field measurements that will be uniquely capable of addressing physics questions on a number of expanding frontiers in condensed matter physics. A 40 T SC magnet would enable more users to run long experiments at peak field with much less power consumption compared with resistive and hybrid magnets. However, realization of such a 40 T SC magnet requires magnet technology well beyond the present state-of-the-art. Initial analysis of different HTS magnet designs, based upon the three presently viable HTS conductors: REBCO, Bi-2212, and Bi-2223, has determined that each technology faces significant challenges. Hence, we decided that four HTS magnet technologies consisting of Insulated REBCO, No-Insulation REBCO, Bi-2212, and Bi-2223 would be developed in parallel and technology gaps based on major risks will be closed in the R&D phase. The candidate technologies will be narrowed down at the decision points. The objective and R&D activities of the 40 T all superconducting user magnet project are presented.